Innovative passive management of the Station Black-Out accident for VVER1000/V446 NPP and development of its emergency operating procedures. (August 2020) - Hosseini, M.M.; Faghihi, F.; Pirouzmand, A.; Rabiee, A.
Abstract: Loss Of Offsite Power (LOOP) accident is one of the most important Design Basis Accidents (DBAs) that originate due to loss of the house-load demands which make serious concerns for each NPP. Moreover, in the case of loss of all diesel generators (due to earthquake, etc.), the accident forwards to the Station Black-Out(SBO). Following and learning the Fukushima accident, the cares have been focused on using internal and/or external water resources for the passive management of the SBO accident. In the current study, passive strategies in the VVER-1000/V446 NPP are proposed using a tank in the secondary loop (called Deaerator) for the SBO management. After RELAP5 modeling benchmarking in the steady-state as well as standard SBO management (which are mentioned in the NPP FSAR), two operational SBO management are proposed herein including "Feeds and Bleeds" (in the primary and secondary loops) and also including a Deaerator tank in the secondary side. The results show that using the Deaerator-water tank of the secondary side as well as feed and bleed, the time available for operators before the core heat-up (i.e. fuel cladding temperature of 1200 °C); extends to 35000 s. Obviously; it gives a good opportunity for plant operators to access further time for using other facilities/methods to avoid core damage.